Núcleos e sítios históricos mineiros: objetivos e ações do órgão de preservação estadual - Roberta Duarte Magalhães (2013)
The management of the historical sites merges with the urban management and the search for the city's development. For these monuments, there is no way to separate the preservation of urban management and heritage protection stop being only a cultural issue to become a multidisciplinary question. With the expansion of the concept of heritage and the incorporation of the urban historical sites as listed by the government, created the need for actions aimed at the conservation of these monuments and taking into account the dynamics of this heritage. The measures adopted in the past to preserve isolated monuments are inefficient for the conservation of urban space, because the inherent characteristic of cities, which are constantly evolving. Information was taken in the documents that are in the physical archives of the State Institute of Historical and Artistic Heritage of Minas Gerais and tables were compiled, in order to facilitate the visualization of commonalities and variations between different sites. Based on comparisons of these tables, it was tried to identify the posture adopted by the agency in dealing with protected sites, in its forty years (1971-2011) of operation. Identifying points of similarity and disagreement between the actions, sought to draw a profile of the management of the historical sites listed by the State of Minas Gerais.